Changes in anaerobic digestion performance and microbial community by increasing SRT through sludge recycling in food waste leachate treatment - Eunyoung Lee; Kyung Jin Min; Ki Young Park (Scientific Reports)
Abstract This study investigates the effects of sludge recycling on anaerobic digestion (AD) performance and microbial community dynamics during food waste leachate treatment. Three reactors with varying solid retention times (SRTs) were operated: a control without sludge recycling (SRT = 20 days) and two experimental setups with SRTs of 40 and 80 days achieved through sludge return. Increasing SRT improved methane production and volatile solids reduction compared to the control, with reductions of 81.0–90.2% at the highest SRT. However, extended SRTs resulted in the accumulation of recalcitrant compounds, such as humic substances, and elevated hydrogen sulfide production due to the increased abundance of sulfate-reducing bacteria (SRB). Microbial analysis showed that higher SRTs enhanced methanogenic diversity, including acetoclastic, hydrogenotrophic, and methylotrophic pathways, while promoting the coexistence of key methanogens such as Methanosaeta, Methanobrevibacter, and Methanoculleus. Although humic substances and SRB abundance increased with higher SRT, methane production remained stable, indicating limited actual inhibition under the studied conditions. Additionally, ATP and specific methanogenic activity tests indicated higher microbial activity at longer SRTs. These findings emphasize the impact of increasing SRT on AD performance, highlighting both benefits in methane yield and challenges in managing inhibitory by-products. Further research should optimize SRT to balance microbial activity, efficiency, and stability in AD processes.